2011
DOI: 10.2174/092986611794927938
|View full text |Cite
|
Sign up to set email alerts
|

Protein Acyltransferase Function of Purified Calreticulin: The Exclusive Role of P-Domain in Mediating Protein Acylation Utilizing Acyloxycoumarins and Acetyl CoA as the Acyl Group Donors

Abstract: The distinct biochemical function of endoplasmic reticulum (ER) protein Calreticulin (CR) catalyzing the transfer of acyl group from acyloxycoumarin to a receptor protein was termed calreticulin transacylase (CRTAase). The present study, unlike the previous reports of others utilizing CR-deficient cells alone, dealt with the recombinant CR domains of Heamonchus contortus (rhCRTAase) in order to examine their CRTAase activity. P-domain of rhCR unlike N- and C-domains was found to be endowed with CRTAase functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Interestingly, we have observed that the full length hCR and the recombinant P-domain possess CRTAase activity, while the N- and C-domains had no CRTAase activity. P-domain catalyzed acetylation of recombinant GST from Schistosoma japonicum (rGST), which have remarkable sequence and structural identity with GST3-3 (an isoform of mu class of rat GST), was analyzed by using the acetylated lysine antibody and by nanoscale LC-MS/MS, which identified the modification of several lysine residues on rGST [62]. …”
Section: Novel Function Of Calreticulin: Protein Acetyltransferasementioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, we have observed that the full length hCR and the recombinant P-domain possess CRTAase activity, while the N- and C-domains had no CRTAase activity. P-domain catalyzed acetylation of recombinant GST from Schistosoma japonicum (rGST), which have remarkable sequence and structural identity with GST3-3 (an isoform of mu class of rat GST), was analyzed by using the acetylated lysine antibody and by nanoscale LC-MS/MS, which identified the modification of several lysine residues on rGST [62]. …”
Section: Novel Function Of Calreticulin: Protein Acetyltransferasementioning
confidence: 99%
“…Also, acetyl CoA is a rather large molecule, with a molecular mass of 810 Da whereas the molecular mass of DAMC is 276 Da.The lysine acetylation is a result of a small alteration of the amino acid side chain in the local secondary structure, it could prevent the long   β -mercaptoethylamine and pantothenate moiety of acetyl CoA from obtaining efficient entry into and exit from the ER lumen. It is worth noting that P-domain catalyzed acetylation of rGST as revealed by LC-MS/MS spectra resulted in the modification of several lysine residues in common, when either DAMC or acetyl CoA was used as the acetyl group donor [62]. …”
Section: Calreticulin As An Acetyl Coa-linked Protein Acetyl Transmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, calreticulin, an ER luminal protein that is mostly known as a Ca +2 -binding chaperone, appears to have acetyl-CoA:lysine acetyltransferase activity in vitro [40]. Whether calreticulin retains acetyltransferase activity in vivo remains to be determined.…”
Section: A Novel Form Of Post-translational Regulation In the Ermentioning
confidence: 99%